Credit Crises, Precautionary Savings, and the Liquidity Trap* - Guerrieri, Veronica; Lorenzoni, Guido (Quarterly Journal of Economics, 2017)
Abstract We study the effects of a credit crunch on consumer spending in a heterogeneous-agent incomplete-market model. After an unexpected permanent tightening in consumers’ borrowing capacity, constrained consumers are forced to repay their debt, and unconstrained consumers increase their precautionary savings. This depresses interest rates, especially in the short run, and generates an output drop, even with flexible prices. The output drop is larger with sticky prices, if the zero lower bound prevents the interest rate from adjusting downward. Adding durable goods to the model, households take larger debt positions and the output response can be larger.